Entanglement and Asymmetric Steering Between Distant Magnon and Mechanical Modes in an Optomagnonic‐Mechanical System. Issue 12 (31st October 2022) - Cheng, Jing; Liu, Yu‐Mu; Wang, Hong‐Fu; Yi, Xuexi
Abstract: A scheme is proposed to generate long‐distance entanglement and asymmetric steering between mechanical oscillator and magnon mode across the frequency difference of ≈10 GHz in an optomagnonic‐mechanical system composed of a magnon, a mechanical oscillator, and two cavities. The calculated results reveal that the long‐distance magnon–phonon entanglement can be achieved due to the fact that the quantum correlation of the two‐mode squeezed vacuum microwave field is successively transferred to the magnon mode and the phonon mode. Moreover, the entanglement is strong enough such that the quantum steering between magnon mode and phonon mode can be achieved in an asymmetric manner. Furthermore, the direction of quantum steering can be flexibly adjusted via changing the magnon damping rate, coupling strength, squeezing parameter, and bath temperature. The proposed scheme provides the possibility for the generation of macroscopic quantum entanglement and steering and has potential applications in quantum information processing. Abstract : A scheme is proposed to generate long‐distance entanglement and asymmetric steering between phonon and magnon modes in an optomagnonic‐mechanical system. The calculated results reveal that long‐distance magnon‐phonon entanglement can be achieved. Furthermore, the direction of steering can be flexibly adjusted via changing the magnon damping rate, coupling strength, and squeezing parameter. The proposed scheme provides the possibility for the generation of macroscopic quantum entanglement and steering and has potential applications in quantum information processing.